Social Entrepreneur Sebagai Core Competence, Tinjauan dari Marketing Perspective - Zuchroh, Imama (STIE Malangkucecwara, 2016)
Long term purpose of this research is to widely spread the theme of Social Entrepreneur. The Social Entrepreneur Model is a unique concept as it combines two contrast concepts which are